2006
DOI: 10.1055/s-2006-924736
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Intraabdominal Desmoplastic Small Round Cell Tumor: A Ten-Year Experience

Abstract: Intrabdominal desmoplastic small round cell tumor is a highly aggressive malignancy with a very poor prognosis. Multiagent chemotherapy usually leads initially to a temporary regression of the tumor, but recurrence is the rule. Radical surgical excision, radiotherapy and peripheral blood stem cell transplantation does not seem to improve prognosis significantly. Despite all therapeutic modalities the outcome is dismal and surgical efforts can be considered only as palliative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…A chromosomal translocation, t (11,22)(p13;q12), involving the EWS and the WT1 genes is highly specific for this tumor. 1 Despite aggressive multimodal treatment, few long-term survivors are reported in most reports.…”
Section: Introductionmentioning
confidence: 99%
“…A chromosomal translocation, t (11,22)(p13;q12), involving the EWS and the WT1 genes is highly specific for this tumor. 1 Despite aggressive multimodal treatment, few long-term survivors are reported in most reports.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lal in its cohort has reported a significant impact of surgery on overall survival with 3 year survival of 58% as compared to 0% in no resectable disease [15], the benefit is greater after complete resection but frequently this act is not feasible due to the extensive involvement as the case of our patient. In contrast, other authors have concluded that surgery has no significant benefit on survival [16,17].…”
Section: Discussionmentioning
confidence: 86%
“…Hassan et al [4] reviewed 12 patients with a DSRCT that were treated in their institution from 1999 to 2001; the median age was 26 years; patients who received complete resection had a median survival of 34 months, compared with 14 months for patients who did not receive surgery. However, in a study by Livaditi et al [5], they analyzed five patients with DSRCT with a median age of 9.6 years and every patient who received surgery relapsed within 2-6 months. We believe that surgery should always be attempted, even when only palliative surgery is feasible, because debulking plays a very important role in the control of local symptoms.…”
Section: Discussionmentioning
confidence: 99%